Pengeringan Kacang Tanah Menggunakan Energi Panas Pembuangan AC - Puspitasari, Indah; Tamrin, Tamrin; Rahmawati, Winda; Warji, Warji (abe.fp.unila.ac.id, 2025)
This study aimed to determine the effectiveness of the peanut drying process by utilizing waste heat from an air conditioner (AC) condenser, using two types of drying systems: horizontal and vertical heat flow. The results showed that the vertical heat flow dryer was more effective, achieving a consistent final moisture content of below 6% (in accordance with SNI 01-3921-1995) within 18 hours, with stable temperatures ranging from 38–40°C and RH below 50%. In contrast, the horizontal heat flow dryer resulted in uneven moisture content (3–14%) with less stable temperature and RH conditions. The drying rate constant (k) was higher in the vertical dryer, indicating a faster rate of water evaporation. Based on these findings, it can be concluded that waste heat from an AC condenser can be utilized as an alternative energy source. The vertical heat flow dryer is more efficient in reducing the moisture content of peanuts to meet storage quality standards.